Political Fictions, Political Realities: Aksumite-Ḥimyarite Relations in the Fourth Century CE - Hatke, George (Antiguo Oriente, 2023)
Beginning in the fourth century CE, rulers of the Ethiopian kingdom of Aksum laid claim to neighboring South Arabia in their royal titles. The problem for historians is that, although the Aksumites are indeed known to have occupied parts of South Arabia during the third century, and to have conquered the region outright in the early sixth century, hard evidence of Aksumite rule during the intervening period is lacking. This being the case, claims of rulership over South Arabia made by fourth-century Aksumite kings would appear to be a political fiction—the reflection, perhaps, of irredentist hopes. However, while irredentist ideology may well have played a role in shaping this political fiction, it fails to account for why such fictitious claims were first put forward when they were. This article makes the case that Gr 27, a Sabaic inscription dating from the early fourth century, provides an answer. The inscription documents the restoration of a structure destroyed by the Aksumites at Ẓafār, capital of the South Arabian kingdom of Ḥimyar. Since this destruction cannot be linked to Aksumite military ventures during the third century, Gr 27 would imply that Aksum invaded South Arabia during the early fourth century. It is here argued that, while this invasion failed to restore Aksumite suzerainty, it provided the pretext for claiming South Arabia as a vassal, a political fiction that Aksumite kings advertised back in Ethiopia.